PERBANDINGAN EFEKTIFITAS MASSAGE DAN KOMPRES HANGAT TERHADAP NYERI PERSALINAN KALA 1 FASE AKTIF - YENNY SAFITRI (Universitas Pahlawan Tuanku Tambusai, 2017)
In the primitive societies, the childbirth is longer and pain, while the people who have advanced 7-14% childbirth without pain and 90% with pain. The purpose of this study was to compare the effectiveness of massage and warm compresses to the first stage of childbirth pain of active phase in Maternity Clinic Ernita years 2015. The clinical research design is quasi-experimental comparison group are time series design. The population in this study are all women giving birth at the maternity clinic Ernita in September of 2015 as many as 45 people. The sample was selected by accidental sampling technique with the study subjects were 30 people who were divided into 2 groups of intervention. The technique of collection data is experiments on the mother inpartu time 1 active phase. Analysis of the data used is the Independent t- test. The results showed faster massage in reducing pain intensity first stage of childbirth is the active phase. The conclusions in this study are more effective massage to reducing pain ofÂ childbirth on the active phase.